User Experience (UX) Components of Mobile Wallets Influencing the Post-adoption Behavior of Millennials in the National Capital Region (NCR) of the Philippines - Alejandrino, Arielle; Baldivas, Alfierie; Etrata, Antonio Jr.; Hipolito, Naomi Grace; Mercado , Chelsea Ayeesha (Journal of Interdisciplinary Perspectives, 2024)
The rapid growth and development of the Internet have changed how people use technology and commerce. Although mobile wallets have become increasingly popular, there is still a lack of research regarding the future viability of the market's adoption of mobile wallets in light of potential risks and emerging alternative concepts. With this, this research investigated how millennials' post-adoption behavior is influenced by the user experience (UX) components in mobile wallet applications, focusing on Filipino millennials. This quantitative study used a descriptive correlational research design to survey 200 regional-based millennials from a population of 1,383,672 mobile wallet users. This study addressed this gap by identifying six vital UX components: aesthetic appeal, security and reliability, ease of use, convenience, information accuracy, and speed and efficiency. Data collection involved an online questionnaire on digital platforms, ensuring data reliability through rigorous testing. Advanced statistical tools, including regression analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM), were utilized for analysis. Despite recognizing the positive contribution of the other components in influencing post-adoption, results have shown that only two, security and reliability and ease of use, of the six identified UX components significantly influence Millennial users' post-adoption behavior towards mobile wallet applications. This result may align with the subject's primary purpose, usage, and motivation, as well as the direct influence of the components on trust, daily utility, risk reduction, competitiveness, regulatory adherence, and user preference adaptation.